Inhibitory serum factor of lymphoproliferative response to allogeneic cells in pregnancy - Daher, Silvia; Fonseca, Flavia; Mattar, Roseane; Musatti, Chloe Camba; Lima, Maria Gerbase de (São Paulo Medical Journal, 1997)
INTRODUCTION: An inhibitory serum factor of mixed lymphocyte culture (MLC) has been associated with successful pregnancy after lymphocyte transfusion in women with unexplained recurrent spontaneous abortions (RSA). OBJECTIVE: Investigate whether the inhibitory serum factor of MLC is essential for a successful pregnancy. METHOD: Sera from 33 healthy pregnant women and from 40 women with RSA were assessed by a one-way MLC in which the woman's lymphocytes were stimulated with her partner's lymphocytes or with third party lymphocytes. RESULTS: An inhibitory serum effect (inhibition > 50% as compared to normal serum) was detected in 45% of the pregnant women who had at least 1 previous parity, in 8% of the primigravidea, in 29% of those with one abortion and in 58% of those with more than one abortion. CONCLUSION: MLC inhibitory serum factor does not seem to be an essential factor for pregnancy development. Therefore, it should not be considered as a parameter for the assessment of RSA patients.